Parent Engagement Interventions Are Not Costless: Opportunity Cost and Crowd Out of Parental Investment. (March 2022) - Robinson, Carly D.; Chande, Raj; Burgess, Simon; Rogers, Todd
Many educational interventions encourage parents to engage in their child's education as if parental time and attention is limitless. Sadly, though, it is not. Successfully encouraging certain parental investments may crowd out other productive behaviors. A randomized field experiment (N = 2, 212) assessed the impact of an intervention in which parents of middle and high school students received multiple text messages per week encouraging them to ask their children specific questions tied to their science curriculum. The intervention increased parent–child at-home conversations about science but did not detectably impact science test scores. However, the intervention decreased parent engagement in other, potentially productive, parent behaviors. These findings illustrate that parent engagement interventions are not costless: There are opportunity costs to shifting parental effort.